Impact of a "Brain Protection Bundle" in Reducing Severe Intraventricular Hemorrhage in Preterm Infants <30 Weeks GA: A Retrospective Single Centre Study - Nishkal Persad; Edmond Kelly; Nely Amaral; Angela Neish; Courtney Cheng; Chun-Po Steve Fan; Kyle Runeckles; Vibhuti Shah (MDPI AG, 2021)
Background: despite advances in perinatal care, periventricular/intraventricular hemorrhage (IVH) continues to remain high in neonatal intensive care units (NICUs) worldwide. Studies have demonstrated the benefits of implementing interventions during the antenatal period, stabilization after birth (golden hour management) and postnatally in the first 72 h to reduce the incidence of IVH. Objective: to compare the incidence of severe intraventricular hemorrhage (IVH ≥ Grade III) before and after implementation of a "brain protection bundle" in preterm infants <30 weeks GA. Study design: a pre- and post-implementation retrospective cohort study to compare the incidence of severe IVH following execution of a "brain protection bundle for the first 72 h from 2015 to 2018. Demographics, management practices at birth and in the NICU, cranial ultrasound results and short-term morbidities were compared. Results: a total of 189 and 215 infants were included in the pre- and post-implementation phase, respectively. No difference in the incidence of severe IVH (6.9% vs. 9.8%, p = 0.37) was observed on the first cranial scan performed after 72 h of age. Conclusion: the implementation of a "brain protection bundle" was not effective in reducing the incidence of severe IVH within the first 72 h of life in our centre.